A Hybrid Fuzzy Multiple Criteria Decision-Making (FMCDM) Approach for Evaluating Quality Management Success Factors in SMEs in Bantul - sulistyo dwi sancoko; Sanjaya Fadil Indra; Kalifia Anna Dina; Artika Selfi (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2026)
Quality Management (QM) plays an important role in improving product quality in handicraft SMEs. However, the implementation of QM in small and medium-scale handicraft businesses is still relatively low. Therefore, this study aims to evaluate the Critical Success Factors (CSFs) of QM in handicraft SMEs in Bantul by using a Hybrid Fuzzy Multiple Criteria Decision-Making (FMCDM) approach. The primary criteria for evaluating QM CSFs were obtained through a literature survey and then processed through the FDM approach by industry and academic experts. Through this approach, the importance of QM CSFs was categorized into three main factors and 16 sub-factors. Two fuzzy MCDM methods were applied, namely fuzzy AHP and TOPSIS, to produce priority rankings for each factor and sub-factor. The results showed that the human factor was ranked first among the three perspectives evaluated. Meanwhile, quality control became the most important sub-factor among the 16 sub-factors. This case study provides useful insights for handicraft SME entrepreneurs to improve the quality of their products. The FMCDM method used in this study can serve as a reference for future research in the field of quality management in SMEs. It is hoped that the results of this study can contribute to improving the quality of products in handicraft SMEs in Bantul and surrounding areas.